Enhancing the Arabic Writing Competency Utilizing Innovative Web-Based Program - Safei, S.; Safei, S. (International Journal of Human and Technology Interaction (IJHaTI), 2021)
Students learning Arabic as a Foreign Language (AFL) find it difficult to transfer and convert linguistic writing abilities into Arabic, implying that they need to get acquainted with the Arabic language to place words in phrases that suit the communication styles. Additionally, Arabic language teachers always complain that teaching Arabic as a foreign language suffers from an acute shortage of educational materials dealing with Arabic writing and Arabic sentence characteristics. In this case, the non-Arabic speaking learners at the intermediate level need a framework to improve their Arabic language competency. The research aims to develop a web-based program (WBP) designed to help learners produce Arabic writing assignments, and essays. With this program, students are able to incorporate structures into their writing and revise them based on the suggested paragraphs, phrases, and Arabic patterns. To develop the framework of the program, different types of vocabulary errors, semantic and rhetorical difficulties among the lower performance of students in Arabic writing tasks will be examined. Both quantitative and qualitative mixed methods, comprising a survey and interview procedures will be adopted in the study. An experiment involving 150-200 pre-university students will also be conducted to demonstrate the different performance between the pretest and the post-test. A comparison in writing activities between the traditional and web-based program approaches will be carried out to test the effectiveness of the program. It is expected that the students using web-based writing program are expected to outperform the regular writing group in most factors, particularly in content, development, and organization. The new innovative writing web-based program is expected to improve students writing skills in Arabic language and a valuable teaching tool for teachers. It is also useful for tourism publications, industrial product translation services and contributes to the new digital media dimensions for societal environment and lifestyle.